2017
DOI: 10.1002/chem.201701298
|View full text |Cite
|
Sign up to set email alerts
|

Employing BINOL‐Phosphoroselenoyl Chloride for Selective Inositol Phosphorylation and Synthesis of Glycosyl Inositol Phospholipid from Entamoeba histolytica

Abstract: The chemical synthesis of glycosyl inositol phospholipids from Entamoeba histolytica is reported. The key feature of this synthesis is a regioselective phosphorylation reaction that occurs through desymmetrization of a myo-inositol derivative with phosphoroselenoyl chloride. A new protecting-group strategy was developed that utilizes allyl and alloc groups to synthesize complex glycolipids bearing unsaturated lipids. These developments provided an efficient synthetic route for various complex inositol phosphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…417 An evaluation of related phosphorus(V)based electrophiles revealed that the highest selectivity (1-OH vs 3-OH) was obtained using phosphorochloridoselenoate 341. 418 These methods were used to prepare inositol phospholipids from the protozoan parasite Entamoeba histolytica.…”
Section: Phosphorylation Of Inositolsmentioning
confidence: 99%
See 1 more Smart Citation
“…417 An evaluation of related phosphorus(V)based electrophiles revealed that the highest selectivity (1-OH vs 3-OH) was obtained using phosphorochloridoselenoate 341. 418 These methods were used to prepare inositol phospholipids from the protozoan parasite Entamoeba histolytica.…”
Section: Phosphorylation Of Inositolsmentioning
confidence: 99%
“…A BINOL-derived chiral phosphitylating agent has been used to achieve the desymmetrization of protected myo -inositol 338 (Scheme ). An evaluation of related phosphorus­(V)-based electrophiles revealed that the highest selectivity (1-OH vs 3-OH) was obtained using phosphorochloridoselenoate 341 . These methods were used to prepare inositol phospholipids from the protozoan parasite Entamoeba histolytica.…”
Section: Reactions With Phosphorus-centered Electrophilesmentioning
confidence: 99%
“…Here, we used the 1,1′‐bi‐2‐naphthol (BINOL)‐derived phosphorylation reagents reported by Murai et al. ; [16, 17] 1D‐ myo ‐inositol‐3/1‐phosphate 4 / 7 was selectively synthesized from myo ‐inositol ( 8 ). In this synthetic strategy, early‐stage chiral differentiation of inositol by regioselective phosphorylation allowed straightforward synthesis without the use of unnecessary chiral auxiliaries or tedious and unreliable diastereomer separation.…”
Section: Resultsmentioning
confidence: 99%
“…In the meantime, other groups have developed related approaches using cyclic asymmetric P-amidites or P-chloridates for desymmetrization. [45][46][47]…”
Section: Account Syn Lettmentioning
confidence: 99%